Reflectance Transformation Imaging as a tool for engineering failure analysis. (November 2019) - Coules, H.E.; Orrock, P.J.; Seow, C.E.
Abstract: Reflectance Transformation Imaging (RTI) is a technique which can be used to record the surface appearance of objects. It can capture a surface's interaction with incident light from different directions and it enables estimation of the surface normal vector. 3D surface profile information can be estimated from RTI datasets using photometric stereo methods. RTI currently has applications in archaeometry and cultural heritage studies but here we discuss the use of RTI in an engineering context: as a tool for failure analysis and particularly for examining failure surfaces in structural materials and components. We demonstrate that RTI can be a practical and low-cost technique for failure analysis, complementing other surface analysis and 3D scanning methods. Graphical abstract: Unlabelled Image Highlights: We report the first uses of Reflectance Transformation Imaging in failure analysis. This technique can be used to distinguish features of material failure surfaces. RTI is a practical, low-cost alternative to conventional macro-optical examination. Composite images from RTI are especially useful for failure interpretation.